Kampanye Vaksinasi Covid-19: Studi Kasus Program Kampanye Vaksinasi Covid-19 oleh Pemerintah Provinsi Kepulauan Bangka Belitung - Nadhifa Rikhansa; Wulan Tri Gartanti (Bandung Conference Series: Public Relations, 2022)
Abstract. The emergency PPKM policy created a number of riots in Indonesia. Therefore, the government needs to provide other policies besides Emergency PPKM to deal with Covid-19 cases in Indonesia. One of them is the Covid-19 Vaccination Program which aims to form a national Herd Immunity. Unfortunately, the number of Indonesians who are willing to be vaccinated against Covid-19 is still far from the Government's target of 70%. For this reason, the government needs some strategies in campaigning for Covid-19 vaccination activities. This study examines the Covid-19 Vaccination Campaign Program by the Provincial Government of the Bangka Belitung Islands. This study aims to determine the Covid-19 Vaccination Campaign Program and its implementation by the Provincial Government of Kep. Bangka Belitung. This research uses qualitative method with constructivist paradigm and case study approach. The concept used as a perspective in this research is the Campaign Technique by Ruslan and Arifin's Communication Strategy. The results of this study explain that the Covid-19 Vaccination Campaign Program by the Provincial Government of the Bangka Belitung Islands is a “Promotive Program” and a "Pick-up" program. This program is carried out by “Satuan Tugas Khusus Vaksinasi Covid-19”. These two programs were carried out because of the threat and strength that Bangka Belitung had in the Covid-19 Vaccination. In its implementation, the Provincial Government of the Bangka Belitung Islands uses participation techniques, associations, integrative techniques, reward techniques, ice sculpture arrangement techniques, and coercion or coercion techniques. The Provincial Government of the Bangka Belitung Islands has also carried out several communication strategies including repetition and canalizing. The content of this campaign message is also educative, persuasive, and informative. Abstrak. Kebijakan PPKM darurat membuat sejumlah kerusuhan di Indonesia. Oleh karenanya, pemerintah perlu memberikan kebijakan lain selain PPKM Darurat untuk mengatasi kasus Covid-19 di Indonesia. Salah satunya adalah Program Vaksinasi Covid-19 yang bertujuan untuk membentuk Herd Immunity nasional. Sayangnya, jumlah masyarakat Indonesia yang bersedia untuk divaksin Covid-19 masih jauh dari target capaian Pemerintah di-angka 70%. Karena itulah, pemerintah memerlukan sebuah upaya dalam mengkampanyekan kegiatan Vaksinasi Covid-19. Penelitian ini meneliti mengenai Program Kampanye Vaksinasi Covid-19 oleh Pemerintah Provinsi Kepulauan Bangka Belitung. Penelitian ini bertujuan untuk mengetahui Program Kampanye Vaksinasi Covid-19 dan implementasinya oleh Pemerintah Provinsi Kep. Bangka Belitung. Penelitian ini menggunakan Metode Kualitatif dengan paradigma konstruktivis serta pendekatan Studi Kasus. Konsep yang digunakan sebagai perspektif dalam penelitian ini adalah Teknik Kampanye oleh Ruslan dan Strategi Komunikasi Arifin. Hasil dari penelitian ini menjelaskan bahwa Program Kampanye Vaksinasi Covid-19 oleh Pemerintah Provinsi Kepulauan Bangka Belitung adalah Program Promotif dan program “Jemput Bola”. Program ini dilakukan oleh Satuan Tugas Khusus Vaksinasi Covid-19. Kedua program ini dilakukan karena ancaman dan kekuatan yang dimiliki Bangka Belitung dalam Vaksinasi Covid-19. Dalam implementasinya, Pemerintah Provinsi Kepulauan Bangka Belitung menggunakan teknik Partisipasi, Asosiasi, teknik integratif, Teknik ganjaran, Teknik penataan patung es, dan Teknik koersi atau paksaan. Pemerintah Provinsi Kepulauan Bangka Belitung juga melakukan beberapa strategi komunikasi diantaranya dalah pengulangan dan Canalizing. Isi pesan kampanye ini juga bersifat edukatif, persuasif, dan informatif.